2012
DOI: 10.1074/jbc.m112.349209
|View full text |Cite
|
Sign up to set email alerts
|

The High and Low Molecular Weight Forms of Hyaluronan Have Distinct Effects on CD44 Clustering

Abstract: Background: The feature of CD44 binding with native high molecular weight hyaluronan (nHA) and hyaluronan oligosaccharides (oHA) is different.Results: nHA induces but oHA reduces CD44 clustering.Conclusion: nHA and oHA have distinct effects on CD44 clustering.Significance: The study provides direct evidence for the different characteristics of CD44 binding with nHA and oHA in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
169
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(180 citation statements)
references
References 63 publications
10
169
0
1
Order By: Relevance
“…Clinically, we suggest using HA as a topical vaginal treatment rather than a bladder treatment, hence we predict that any flushing effects would be reduced. One method by which UPEC has been reported to infect the murine urinary tract is through attaching to CD44 receptors44 that also bind HA 45. Although receptor masking by HMW HA may have functioned in reducing UPEC infection in vivo , specific localisation of UPEC to the epithelial tight junctions was less supportive of such a mechanism operating in the human urothelial cell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, we suggest using HA as a topical vaginal treatment rather than a bladder treatment, hence we predict that any flushing effects would be reduced. One method by which UPEC has been reported to infect the murine urinary tract is through attaching to CD44 receptors44 that also bind HA 45. Although receptor masking by HMW HA may have functioned in reducing UPEC infection in vivo , specific localisation of UPEC to the epithelial tight junctions was less supportive of such a mechanism operating in the human urothelial cell model.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be excluded, however, that these data were prejudiced by the signalling activities of receptors persisting following incomplete gene knockdown. HMW HA treatment is not only associated with receptor binding but also receptor clustering that functions, potentially, to stabilise cell membrane transporters and/or receptors 45. Hence, if activated urothelial TLR5 and CD44 receptors cluster similarly in response to flagellin and HA, then the outcome supports signal amplification through either better retention of their respective ligands or increased rebinding.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of inflammation, HMM HA is broken down into LMM HA, which exhibits multiple pro-inflammatory effects on cells and tissues [13, 18, 26]. HMM HA is broken down into LMM HA by the combined actions of hyaluronidases and reactive oxygen species (ROS) that are produced by inflammatory cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that LMM HA exhibits pronounced biological effects on cells and in tissues [13, 18]. Most importantly, LMM HA has multiple pro-inflammatory effects not observed for HMM HA [15, 26]. In fact, HMM HA can block the pro-inflammatory effects of LMM HA and help support tissue integrity [13, 26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation